A Cross-sectional Survey and Cross-sectional Clinical Trial to Determine the Prevalence and Management of Eye Movement Disorders and Vestibular Dysfunction in Post-Stroke Patients in the Sub-Acute Phase: Protocol - van Wyk, Andoret; Eksteen, Carina A.; Becker, Piet J.; Heinze, Barbara M. (Frontiers in Neurology, 2016)
Introduction: Visual impairment, specifically eye movement disorders and vestibular dysfunction may have a negative influence on the functional recovery in post stroke patients. This type of sensory dysfunction may further be associated with poor functional outcome in patients post stroke. Methods: In phase 1 a cross-sectional survey (n = 100) will be conducted to determine the prevalence of eye movement disorders and vestibular dysfunction in patients that sustained a stroke. A cross-sectional clinical trial (n = 60) will be conducted during phase 2 of the study to determine the effect of the combination of vestibular rehabilitation therapy (VRT) and visual scanning exercises (VSE) (experimental group) integrated with task-specific activities compared to the effect of task-specific activities as an intervention (control group) on patients that present with eye movement impairment and central vestibular dysfunction post-stroke. An audiologist will assess; (a) visual acuity (static and dynamic); (b) nystagmus; (c); saccadic eye movements; (d) smooth pursuit eye movements; (e) vestibulo-ocular reflex; and (f) saccular, utricular and vestibular nerve function. An independent physiotherapist will assess; (1) cognitive function; (2) residual oculomotor visual performance; (3) visual-perceptual system; (4) functional balance; (5) a patient’s ability to modify gait in response to changing task demands; (6) functional ability; and (7) presence of anxiety and/or depression and (8) level of participation in physical activity. Ethics and dissemination: Ethics approval has been obtained from the Ethics Committee of the Faculty of Health Sciences at the University of Pretoria (UP) (374/2015). The study will be submitted as fulfilment for the PhD degree at UP. Dissemination will include submission to peer-reviewed professional journals and presentation at congresses. Training of rehabilitation team members on the integration of VSE and VRT into task-specific activities in rehabilitation will be done if the outcome of the experimental group’s functional perpformance is clinically and statistically significantly better than the control group on the Barthel Index. Trial Registration: Pan African Clinical Trials Registry (PACTR201509001223262).